Cardiac arrest resuscitation policy and practice: A survey of Western Australian hospitals - Rogal, S.; Finn, Judith; Jacobs, Ian (Australian Nursing Federation, 2009)
Objective: To determine if cardiopulmonary resuscitation (CPR) policy and practice in Western Australian (WA) hospitals changed since the release of an operational directive from the WA Department of Health. Design: Cross sectional postal survey conducted in 2008 compared to the results of the 2001 survey. Setting: Western Australian public hospitals containing ten or more beds. Subjects: 66 WA hospitals in 2001; 59 WA hospitals in 2008. Main outcome measures: Characteristics of defibrillators; CPR and defibrillation training and assessment; who was permitted to undertake defibrillation; type of cardiac arrest management team, whether data was routinely collected on cardiac arrests and outcomes and any other issues related to resuscitation policy and practice. Results: There was a 15% increase in the number of hospitals with AEDs (15% difference; 95% CI 10%, 29%; p=0.04) and an increase in proportion of hospitals that allowed nurses to defibrillate from 74% to 98% (24% difference; 95% CI 14%, 34%; p<0.001). There was an increase in the uptake of ARC guidelines (15% difference; 95% CI 5%, 25%; p<0.01). Conclusions: Since the release of the operational directive following the 2001 survey more hospitals have purchased AEDs and there has been an increase in the proportion of hospitals 'allowing' nurses to defibrillate. However, given the overwhelming evidence that time to defibrillation is the major determinant of likelihood of survival in cardiac arrest, it is indefensible that that not all hospitals can provide first responder defibrillation 24 hours per day, seven days per week.